Hot Subdwarf Stars Identified in LAMOST DR8 with Single-lined and Composite Spectra - Zhenxin Lei; Ruijie He; Péter Németh; Joris Vos; Xuan Zou; Ke Hu; Huaping Xiao; Huahui Yan; Jingkun Zhao (The Astrophysical Journal, 2023)
A total of 222 hot subdwarf stars were identified with LAMOST DR8 spectra, among which 131 stars show composite spectra and have been decomposed, while 91 stars present single-lined spectra. Atmospheric parameters of all sample stars were obtained by fitting hydrogen (H) and helium (He) line profiles with synthetic spectra. Two long-period composite sdB binaries were newly discovered by combining our sample with the non-single-star data from Gaia DR3. One of the new systems presents the highest eccentricity (i.e., 0.5 ± 0.09) among known wide sdB binaries, which is beyond model predictions. A total of 15 composite sdB stars fall in the high-probability binary region of the RUWE−AEN plane and deserve priority follow-up observations to further study their binary nature. A distinct gap is clearly presented among temperatures of cool companions for our composite-spectrum sample, but we could not come to a conclusion as to whether this feature is connected to the formation history of hot subdwarf stars before their binary natures are confirmed.